Collaborative Project-Based Learning with Eco-Friendly Product Theme: Improving Students’ Conceptual Understanding of Basic Chemical Laws - Devita Marlina Marlina Venessa; Ariyatun Ariyatun; Vida Zenitha Sudariasri; Fera Kuraysia; Dira Ayu Annisa (Universitas Khairun, 2026)
ABSTRACT. Understanding basic chemistry concepts is an important fundamental concept in high school chemistry education. This concept is very difficult to integrate into real-world phenomena, as learning generally emphasizes memorization and has minimal connection to real-world phenomena. Based on this, research to analyze the effectiveness of the Collaborative Cross-Disciplinary Chemistry-Physics Project-Based Learning (PJBL) model with 10 Eco-Friendly Product Project themes to improve understanding of basic chemistry concepts needs to be conducted. The method used was a quasi-experiment with a one group pretest-posttest design on 55 high school students in Jakarta. The data, in the form of pretest-posttest scores, were analyzed using descriptive statistics, paired t-tests, Pearson's correlation, and N-Gain. The results showed an increase in the average score from 66.36 on the pretest to 85.55 on the posttest, with the percentage of mastery increasing from 45.45% to 90.91%. The decrease in standard deviation indicates a more even distribution of scores. Statistical analysis shows a statistically significant increase (p<0.001) and a moderate positive correlation between the initial and final scores. The group performance assessment data during the implementation of PjBL shows that each group demonstrated adequate understanding in relating chemistry concepts to the projects they worked on, as well as good ability based on the five predetermined criteria.